2022
DOI: 10.1177/11206721221092224
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between three different high fluence UVA levels in corneal collagen cross-linking for treatment of experimentally induced fungal keratitis in rabbits

Abstract: Introduction The aim of this study was to compare the efficacy of Photo-Activated Chromophore for Keratitis – Corneal Collagen Cross-linking (PACK-CXL) of three different total UVA fluence levels and topical voriconazole in treatment of fungal keratitis experimentally induced in rabbits. Methods This is an interventional experimental study including both eyes of 16 rabbits (32 eyes). Fungal keratitis was induced by intrastromal injection of Fusarium Solani into the cornea. The rabbits were then divided into fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Awad et al used rabbit models to test the efficiency of different PACK-CXL protocols on fungal keratitis, vs. Voriconazole as control. They found all protocols including the standard Voriconazole treatment to be effective with no statistically significant difference between them ( Awad et al, 2022 ). Hafezi et al compared antimicrobial therapy and PACK-CXL using of fluences of either 5.4 J/cm 2 or 7.2 J/cm 2 in a phase 3 trial that involved patients with infectious keratitis ( Hafezi et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awad et al used rabbit models to test the efficiency of different PACK-CXL protocols on fungal keratitis, vs. Voriconazole as control. They found all protocols including the standard Voriconazole treatment to be effective with no statistically significant difference between them ( Awad et al, 2022 ). Hafezi et al compared antimicrobial therapy and PACK-CXL using of fluences of either 5.4 J/cm 2 or 7.2 J/cm 2 in a phase 3 trial that involved patients with infectious keratitis ( Hafezi et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…More in vitro studies support this result ( Lu et al, 2023 ). In vivo studies examining high fluences on infectious keratitis, however, are scarce ( Nateghi Pettersson et al, 2019 ; Knyazer et al, 2021 ; Hafezi et al, 2022a ; Awad et al, 2022 ; Hafezi et al, 2022b ; Marrie et al, 2023 ), mostly on animal models or human case reports. Our first aim is to show the therapeutic benefit of high fluence PACK-CXL in a case series.…”
Section: Introductionmentioning
confidence: 99%
“…Hafezi et al 136 recently used UVA of 9 mW/cm 2 for either 10 min, 13 min, or 20 s with a total fluence of either 5.4 J/cm 2 or 7.2 J/cm 2 . Higher fluences of UVA (up to 15 J/cm 2 ) were tested by Awad et al 137,138 and gave better clinical, microbiological, and pathological outcomes on rabbit eyes. Repeated high fluence PACK-CXL was reported by Hafezi et al 134 Four out of 9 eyes showed good response and infection was completely halted and scared down.…”
Section: Rose Bengal Photo-dynamic Antimicrobial Therapy (Pdat)mentioning
confidence: 99%